Microgravity, Stem Cells, and Embryonic Development: Challenges and Opportunities for 3D Tissue Generation - Andreazzoli, Massimiliano; Angeloni, Debora; Broccoli, Vania; Demontis, Gian C. (Frontiers in Astronomy and Space Sciences, 2017)
Space is a challenging environment for the human body, due to the combined effects of reduced gravity (microgravity) and cosmic radiation. Known effects of microgravity range from the blood redistribution that affects the cardiovascular system and the eye to muscle wasting, bone loss, anemia and immune depression. About cosmic radiation, the shielding provided by the spaceship hull is far less efficient than that afforded at ground level by the combined effects of the Earth atmosphere and magnetic field. The eye and its nervous layer (the retina) are affected by both microgravity and heavy ions exposure. Considering the importance of sight for long-term manned flights, visual research aimed at devising measures to protect the eye from environmental conditions of the outer space represents a special challenge to meet. In this review we focus on the impact of microgravity on embryonic development, discussing the roles of mechanical forces in the context of the neutral buoyancy the embryo experiences in the womb. At variance with its adverse effects on the adult human body, simulated microgravity may provide a unique tool for understanding the biomechanical events involved in the development and assembly in vitro of three-dimensional (3D) ocular tissues. Prospective benefits are the development of novel safety measures to protect the human eye from cosmic radiation in microgravity during long-term manned spaceflights in the outer space, as well as the generation of human 3D-retinas with its supporting structures to develop innovative and effective therapeutic options for degenerative eye diseases.